Pengaruh Penggunaan Google Classroom dalam Pembelajaran Daring selama Covid-19 di SMP Negeri 41 Palembang - Sarkol, Primos (Yayasan Sembilan Pemuda Indonesia, 2021)
The purpose of this study was to determine the use of Google Classroom in online learning during Covid-19 at SMP Negeri 41 Palembang, to determine the creativity of teachers in teaching using Google Classroom in online learning during Covid-19 at SMP Negeri 41 Palembang, as well as the obstacles experienced by teachers in implementing Google Classroom application for online mathematics learning during Covid-19 at SMP Negeri 41 Palembang. The sample in this study were all teachers at SMP Negeri 41 Palembang. Data collection techniques used are interviews and documentation. Data analysis techniques consist of data reduction, data presentation, and concluding. While checking the validity of the data using source triangulation. The results of the study reveal that: (1) There is an effect of using google classroom in online learning in the Covid-19 Pandemic; (2) The average creativity of teachers in teaching increases even with different methods; (3) The obstacles found in learning to use google classroom are influenced by the lack of communication with students and the internet network that has not been spread evenly.